2021
DOI: 10.3389/phrs.2021.1603960
|View full text |Cite
|
Sign up to set email alerts
|

The Burden of Drug Abuse in Nigeria: A Scoping Review of Epidemiological Studies and Drug Laws

Abstract: Background: The burden of drug abuse is becoming a public health concern in Nigeria. Preventive measures should include identifying the root causes of the burden for targeted intervention. We, therefore, aim to conduct a scoping review of the literature to summarize the findings of epidemiological studies on drug abuse and provisions of drug laws in Nigeria. The review also provides appropriate recommendations as interventions for prevention.Methods: We conducted a systematic search of the literature on PubMed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
57
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 16 publications
6
57
1
Order By: Relevance
“…The prevalence of neurological disorders vary by condition, but epilepsy, for instance, has been estimated at 8 per 1000 people [ 9 ]. Substance-use disorders have been estimated between 20 and 40% among youths and 14% in the general population [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of neurological disorders vary by condition, but epilepsy, for instance, has been estimated at 8 per 1000 people [ 9 ]. Substance-use disorders have been estimated between 20 and 40% among youths and 14% in the general population [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Polysubstance use was common in the general population, and high-risk users were defined as those who had used opioids, crack/cocaine, or amphetamines at least five times in the past month. Numerous reasons are provided for their use among the population including as a coping mechanism for stress [57].…”
Section: Substance Use and Hiv Prevalence Among Populations In Nigeriamentioning
confidence: 99%
“…Findings on psychoactive substance use among university students in Nigeria had exposed that 20% of students with mean age of 20 years had used alcoholic beverages, while the consumption of marijuana and /or opoids including tramadol and codeine was 16.0% [28]. A scoping review from epidemiological studies around substance use in Nigeria had revealed that the substance use among students and youth were 20-40% and 20.9% respectively; cannabis, cocaine, amphetamine, heroin, diazepam, codeine, cough syrup and tramadol were implicated as the most commonly substances being used [29]. In a cross-sectional study conducted among women farmers in Adamawa State on psychoactive substance use revealed that cannabis and tramadol were the mostly used substances due to affordability and availability [30].…”
Section: Introductionmentioning
confidence: 99%